Experimental multimedia systems for interactivity and strategic innovation - Deliyannis, Ioannis 1975-; Kostagiolas, Petros; Banou, Christina 1971 (Advances in data mining and database management (ADMDM) book series, 2016)
This book presents the next evolutionary step of multimedia where interactivity meets targeted creativity and experimentation and provides the basic framework for experimental multimedia through case studies that allow the reader to appreciate the design of multimedia systems